2022
DOI: 10.1136/postgradmedj-2022-141573
|View full text |Cite
|
Sign up to set email alerts
|

High level of lactate dehydrogenase and ischaemia–reperfusion injury regulate the multiple organ dysfunction in patients with COVID-19

Abstract: BackgroundMultiple organ damage has been observed in patients with COVID-19, but the exact pathway is not known. Vital organs of the human body may get affected after replication of SARS-CoV-2, including the lungs, heart, kidneys, liver and brain. It triggers severe inflammation and impairs the function of two or more organ systems. Ischaemia–reperfusion (IR) injury is a phenomenon that can have disastrous effects on the human body.MethodsIn this study, we analysed the laboratory data of 7052 hospitalised pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…16 In individuals with COVID-19, gender is a significant risk factor for disease severity and mortality. 17 According to a retrospective study, males and females were equally susceptible, but males were more likely to die and made up around 2.4 times more compared to females among deceased patients. 18 In contrast to global examinations, females were less impacted by COVID-19 in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…16 In individuals with COVID-19, gender is a significant risk factor for disease severity and mortality. 17 According to a retrospective study, males and females were equally susceptible, but males were more likely to die and made up around 2.4 times more compared to females among deceased patients. 18 In contrast to global examinations, females were less impacted by COVID-19 in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high CRP was observed in the death group compared with the survival group, LDH was selected by LASSO regression as an important feature instead of CRP. It is widely thought that the LDH concentration is a useful marker in evaluating the prognosis of different types of pneumonia, such as pneumocystis jiroveci pneumonia and community-acquired pneumonia, and a significant correlation between LDH and CRP in COVID-19 has been documented ( Ashraf et al., 2022 ). We also observed a moderate correlation between LDH and CRP (r=0.562), which might explain why the lasso model did not recognize CRP as an important feature.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that SARS-CoV-2 infection is associated with a high risk for thrombotic complications, including the acute limb ischemia (ALI) [48]. Ashraf et al [49] linked ischemia-reperfusion (IR) injury to multiple organ damage by SARS-CoV-2, suggesting COVID-19 may cause a reduction in oxygen towards an organ, which leads to IR injury.…”
Section: Pharmacogenomic Analyses Of Ivermectin and The Selected 6 An...mentioning
confidence: 99%